2019
DOI: 10.1108/imds-10-2018-0430
|View full text |Cite
|
Sign up to set email alerts
|

Integrating theories to predict clothing purchase on SNS

Abstract: Purpose The purpose of this paper is to design and test a conceptual model integrating uses and gratifications (UGT), self-image congruity (SIC), and theory of planned behavior (TPB) theories to identify the drivers that lead users to develop intentions to purchase clothing products through social networking sites (SNS). Design/methodology/approach Using an online questionnaire, data were collected from customers of clothing products who visit the SNS of their preferred clothing brands (n=1,003). Empirical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
(111 reference statements)
2
11
0
Order By: Relevance
“…To achieve this, we investigated a novel conceptual model which explains the impact of social networking sites advertisements, on consumer purchases decision: mediated by brand. As a primary contribution, this research showed that there was a positive relationship between social networking sites advertisement and consumer purchase decision, these results are consistent with previous studies, where the researcher found that SNS had a significant direct effect on consumer purchase intention towards clothes brands in Spain (Pujadas-Hostench et al, 2019a, 2019b. These results indicated that, when the consumer realizes the clothes brand advertisement in SNS they would be willing and interested in that brands which led them make a decision in purchasing that specific clothes brand which in turn resulting in their actual baying behavior (Touchette et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…To achieve this, we investigated a novel conceptual model which explains the impact of social networking sites advertisements, on consumer purchases decision: mediated by brand. As a primary contribution, this research showed that there was a positive relationship between social networking sites advertisement and consumer purchase decision, these results are consistent with previous studies, where the researcher found that SNS had a significant direct effect on consumer purchase intention towards clothes brands in Spain (Pujadas-Hostench et al, 2019a, 2019b. These results indicated that, when the consumer realizes the clothes brand advertisement in SNS they would be willing and interested in that brands which led them make a decision in purchasing that specific clothes brand which in turn resulting in their actual baying behavior (Touchette et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Te dominant dissemination and development of SNS create various derivative areas beyond the unique functions and roles of SNS. Many sellers and buyers trade goods through social media platforms [3]. Political parties promote their policies through social media and demonstrate the excellence of their candidates [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have not refected all three contexts in a balanced way when illuminating SNS user behavior. Tey have introduced only utilitarian context and hedonic context [7,25], hedonic context and social context [19], personal inclinations and social impacts [3,6,26], social factors and security [27], or the impact of COVID-19 [28] in the process of building the theoretical models. However, the current study focuses on the unique roles of SNS and examines user behavior by employing utilitarian, hedonic, and social factors.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of UGT explains how people use media, and investigates the various gratificationsthatdrivemediause [14].UGTemphasizesthevariouseffectsofgratifications on people's motivation to engage in behaviors [15]. Moreover, several research studiesusedUGTtoexamineandexplorewhyindividualsusedsocialmediaandthe benefitsgainedwhenconsumingmedia,connecting,andalsoexchangingcontentand knowledge from those media using various media [16]. Users will continue to interact with social media if their satisfaction and desires are in line with the platform [17].…”
Section: Uses and Gratification Theorymentioning
confidence: 99%